Differences Between Skilled Nursing Facilities in Risk of Subsequent Long‐Term Care Placement. Issue 10 (14th April 2018) - Goodwin, James S.; Li, Shuang; Middleton, Addie; Ottenbacher, Kenneth; Kuo, Yong‐Fang
Abstract : See related editorial by Vincent Mor et al . Abstract : Objectives: To determine how the risk of subsequent long‐term care (LTC) placement varies between skilled nursing facilities (SNFs) and the SNF characteristics associated with this risk. Design: Population‐based national cohort study with participants nested in SNFs and hospitals in a cross‐classified multilevel model. Setting: SNFs (N=6, 680). Participants: Fee‐for‐service Medicare beneficiaries (N=552, 414) discharged from a hospital to a SNF in 2013. Measurements: Participant characteristics from Medicare data and the Minimum Data Set. SNF characteristics from Medicare and Nursing Home Compare. Outcome was a stay of 90 days or longer in a LTC nursing home within 6 months of SNF admission. Results: Within 6 months of SNF admission, 10.4% of participants resided in LTC. After adjustments for participant characteristics, the SNF where a participant received care explained 7.9% of the variance in risk of LTC, whereas the prior hospital explained 1.0%. Individuals in SNFs with excellent quality ratings had 22% lower odds of transitioning to LTC than those in SNFs with poor ratings (odds ratio=0.78, 95% confidence interval=0.74–0.84). Variation between SNFs and associations with quality markers were greater in sensitivity analyses limited to individuals least likely to require LTC. Results were essentially the same in a number of other sensitivity analyses designed to reduce potential confounding. Conclusion: Risk of subsequent LTC placement, an important and negatively viewed outcome for older adults, varies substantially between SNFs. Individuals in higher‐quality SNFs are at lower risk.